Spoilers as (Un)Wanted Information: How Reader’s Engagement with Paratextual Material Affects Wellbeing - Romaguera Gabriel (Open Information Science, 2022)
Engaging with a text allows one to enter a flow state through the actions or reading/viewing a narrative or event. Spoilers, which provide information about the text but bypassing the intended reading path as set out by the author, can serve to interrupt a state of flow, dissuade one from even attempting to interact with the text at hand, or catch one’s eye to an interesting aspect that would normally be hidden. In this study, I classify spoilers through Genette’s concept of paratexts and how they affect one’s wellbeing through the notions of Seligman’s PERMA theory (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishments, with specific focus on aspects of engagement. Throughout this work, I denote different aspects of spoilers as found in examples of popular culture to establish how these paratexts can hinder or help in one’s engagement with a potential text and how these can affect one’s wellbeing. In order to help readers avoid unwanted spoilers. I also include how different elements of digital media can be adapted in order that one obtain such information only if one desires it to make an informed decision as to whether or not engage with a specific text.